(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Understanding the role of English language in post-colonial translation in India is remarkable; how and when English language reached India and how it was received by Indians, what was its status then and what is its status now also matters. The status of English language before 1757 in India, its usage in East India Company Rule from 1757 to 1857 and in colonial period from 1857 to 1947 could be understood. The acts of translations have continued even after independence when English has become an important vehicle of transmitting ideas throughout the country. English has become a link language between various Indian languages. More and more writers demand to be translated into English instead of Hindi or other Indian languages. The demand is high because translation into English gives them a wider reach and a dual readership.